Polythiophene conductive polymer, positive electrode slurry, positive electrode plate, preparation method of positive electrode plate, battery monomer, battery and electric device

By using polythiophene conductive polymer in the positive electrode sheet of the battery and performing blue light irradiation, the problem of taking into account both high energy density and rate performance is solved, and the overall performance of the battery is improved.

CN119241815AActive Publication Date: 2025-01-03CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310806166.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03
Estimated Expiration
2043-07-03

AI Technical Summary

Technical Problem

Existing batteries have difficulties in combining high energy density and good rate performance, especially the flexibility and processing performance of the positive electrode sheet, which leads to insufficient wetting properties of the electrolyte and limited rate performance of the battery.

Method used

Polythiophene conductive polymer is used as the key component of the positive electrode sheet, and the heating efficiency of the polythiophene conductive polymer is improved through blue light irradiation, stress release, and a high porosity film layer is formed, which improves the wetting and adhesion of the electrolyte. , reduce the resistance.

Benefits of technology

The cohesion, adhesion and processing performance of the positive electrode sheet are improved, the rate performance and energy density of the battery are enhanced, and the internal resistance of the battery is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241815A_ABST
    Figure CN119241815A_ABST
Patent Text Reader

Abstract

The invention discloses a polythiophene conductive polymer, positive electrode slurry, a positive electrode plate, a preparation method of the positive electrode plate, a battery monomer, a battery and an electric device. The polythiophene conductive polymer comprises at least one of a first structural unit as shown in a formula (1), a second structural unit as shown in a formula (2), a third structural unit as shown in a formula (3) and a fourth structural unit as shown in a formula (4). # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a polythiophene conductive polymer, a positive electrode slurry, a positive electrode plate and a preparation method thereof, a battery cell, a battery and an electrical device. Background Art

[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. In recent years, with the continuous expansion of battery application fields, the requirements for the comprehensive performance of batteries have also continued to increase. However, how to make the battery have both high energy density and good processing performance and rate performance is still a technical problem that needs to be solved at present. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art. Summary of the invention

[0003] The present application provides a polythiophene conductive polymer, a positive electrode slurry, a positive electrode plate and a preparation method thereof, a battery cell, a battery and an electrical device, which can enable the battery to have both high energy density and good rate performance.

[0004] In a first aspect, the present application provides a polythiophene conductive polymer, comprising: a first structural unit represented by formula (1); and at least one of a second structural unit represented by formula (2), a third structural unit represented by formula (3), and a fourth structural unit represented by formula (4).

[0005]

[0006] R 11 Including C1-C8 alkyl or C1-C8 alkyl alkoxy, R 12 Including hydrogen atom or C1-C3 alkyl; R 21 Including C1-C5 alkylene, R 22 includes a hydrogen atom or a C1-C3 alkyl group, M includes a monovalent metal; R 31 Including C1-C5 alkylene, R 32 Including hydrogen atom or C1-C3 alkyl; R 41 Including C1-C5 alkylene, R 42 Including the residue of diisocyanate, R 43 Including C2-C6 alkylene, R 44 Including C1-C3 alkyl, R 45 Including a hydrogen atom or a C1-C3 alkyl group, s≥1; n1>0; n2≥0, n3≥0, n4≥0, and n2+n3+n4>0.

[0007] By making the positive electrode plate include the polythiophene conductive polymer of the present application, the cohesion and adhesion of the positive electrode plate can be improved, the electrolyte wettability of the positive electrode plate can be improved, and the processing performance and dynamic performance of the positive electrode plate can be improved, thereby enabling the battery to have both high energy density and good rate performance.

[0008] In any embodiment, the number average molecular weight of the polythiophene conductive polymer is 3000-45000, and can be 5000-34000. When the number average molecular weight of the polythiophene conductive polymer is within the above range, the positive electrode sheet can have good flexibility, thereby improving the processing performance of the positive electrode sheet and the battery; in addition, the positive electrode slurry can also have good dispersibility, thereby better improving the performance of the battery.

[0009] In any embodiment, the polythiophene conductive polymer satisfies at least one of the following conditions (1) to (13):

[0010] (1)R 11 Including C4-C6 alkyl or C4-C6 alkylalkoxy;

[0011] (2)R 12 Includes hydrogen atoms;

[0012] (3)R 21 Including C1-C3 alkylene;

[0013] (4)R 22 Includes hydrogen atoms;

[0014] (5) M includes Li and / or Na;

[0015] (6)R 31 Including C1-C3 alkylene;

[0016] (7)R 32 Includes hydrogen atoms;

[0017] (8)R 41 Including C1-C3 alkylene;

[0018] (9)R 42 Including R a Substituted or unsubstituted C1-C6 alkylene, and one of the following groups:

[0019]

[0020] # indicates the connection position, R a Each independently includes C1-C3 alkyl, R b Each independently includes a C1-C3 alkyl group, p represents an integer of 0-4, and q represents an integer of 0-6;

[0021] (10)R 43 Includes the following groups:

[0022]

[0023] (11)R 44 Includes methyl;

[0024] (12)R 45 Includes hydrogen atoms;

[0025] (13)s is 3-140, and can be optionally 10-90.

[0026] In any embodiment, n2>0, n3=0, n4=0; or, n2=0, n3>0, n4=0; or, n2=0, n3>0, n4>0; or, n2>0, n3>0, n4>0.

[0027] The second aspect of the present application provides a positive electrode slurry, comprising a solvent and a non-solvent component, wherein the non-solvent component comprises a positive electrode active material, a positive electrode binder and a positive electrode conductor, wherein the positive electrode conductor comprises the polythiophene conductive polymer of the first aspect of the present application.

[0028] In any embodiment, the solvent includes a non-aqueous solvent, which may optionally include N-methylpyrrolidone, and the positive electrode binder includes an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65; optionally, 0.40≤n1 / (n1+n2+n3+n4)≤0.60. When n1 / (n1+n2+n3+n4) is within the above range, the dispersibility of the non-aqueous positive electrode slurry can be improved, the processing performance of the prepared positive electrode sheet can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0029] In any embodiment, the positive electrode binder includes one or more of polyvinylidene fluoride, polyimide, and polyurethane.

[0030] In any embodiment, the positive electrode binder includes an oily binder, and 0≤n2 / (n1+n2+n3+n4)≤0.25, and optionally, 0≤n2 / (n1+n2+n3+n4)≤0.10. This can improve the dispersibility of the non-aqueous positive electrode slurry and improve the dynamic performance of the positive electrode sheet and the battery.

[0031] In any embodiment, the positive electrode binder includes an oily binder, and 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60. When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0032] In any embodiment, the positive electrode binder includes an oily binder, and 0≤n4 / (n3+n4)≤0.20, optionally, 0<n4 / (n3+n4)≤0.15. When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0033] In any embodiment, the solvent includes water, the positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25; optionally, 0.08≤n1 / (n1+n2+n3+n4)≤0.22. When n1 / (n1+n2+n3+n4) is within the above range, the dispersibility of the aqueous positive electrode slurry can be improved, the bonding force and processing performance of the prepared positive electrode sheet can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0034] In any embodiment, the positive electrode binder includes one or more of carboxymethyl cellulose and its derivatives, sodium alginate, polyacrylic acid and its derivatives, agarose, gelatin, carrageenan, xanthan gum, guar gum, polyvinyl alcohol, and polyacrylamide.

[0035] In any embodiment, the positive electrode binder includes an aqueous binder, and 0.15≤n2 / (n1+n2+n3+n4)≤0.45, optionally, 0.25≤n2 / (n1+n2+n3+n4)≤0.40. When n2 / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0036] In any embodiment, the positive electrode binder includes an aqueous binder, and 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60. When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0037] In any embodiment, the positive electrode binder includes an aqueous binder, and 0≤n4 / (n3+n4)≤0.20, optionally, 0.04≤n4 / (n3+n4)≤0.15. When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0038] In any embodiment, the positive electrode active material includes one or more of lithium transition metal oxides, lithium-containing phosphates, and modified compounds thereof.

[0039] In any embodiment, the positive electrode slurry further includes a second conductive agent, and the second conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0040] In any embodiment, the content of the polythiophene conductive polymer in the non-solvent component is 0.2-4%, optionally 0.5-3%, based on the total weight of the non-solvent component.

[0041] The third aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material, a positive electrode binder and a positive electrode conductor, and the positive electrode conductor comprises the polythiophene conductive polymer of the first aspect of the present application.

[0042] In any embodiment, the positive electrode binder includes an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65; optionally, 0.40≤n1 / (n1+n2+n3+n4)≤0.60. When n1 / (n1+n2+n3+n4) is within the above range, the uniformity of the positive electrode film layer can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0043] In any embodiment, the positive electrode binder includes one or more of polyvinylidene fluoride, polyimide, and polyurethane.

[0044] In any embodiment, the positive electrode binder includes an oily binder, and 0≤n2 / (n1+n2+n3+n4)≤0.25, optionally, 0≤n2 / (n1+n2+n3+n4)≤0.10. This can improve the uniformity of the positive electrode film layer and the dynamic performance of the positive electrode sheet and the battery.

[0045] In any embodiment, the positive electrode binder includes an oily binder, and 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60. When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0046] In any embodiment, the positive electrode binder includes an oily binder, and 0≤n4 / (n3+n4)≤0.20, optionally, 0<n4 / (n3+n4)≤0.15. When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0047] In any embodiment, the positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25; optionally, 0.08≤n1 / (n1+n2+n3+n4)≤0.22. When n1 / (n1+n2+n3+n4) is within the above range, the uniformity of the positive electrode film layer can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0048] In any embodiment, the positive electrode binder includes one or more of carboxymethyl cellulose and its derivatives, sodium alginate, polyacrylic acid and its derivatives, agarose, gelatin, carrageenan, xanthan gum, guar gum, polyvinyl alcohol, and polyacrylamide.

[0049] In any embodiment, the positive electrode binder includes an aqueous binder, and 0.15≤n2 / (n1+n2+n3+n4)≤0.45, optionally, 0.25≤n2 / (n1+n2+n3+n4)≤0.40. When n2 / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0050] In any embodiment, the positive electrode binder includes an aqueous binder, and 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60. When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0051] In any embodiment, the positive electrode binder includes an aqueous binder, and 0≤n4 / (n3+n4)≤0.20, optionally, 0.04≤n4 / (n3+n4)≤0.15. When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0052] In any embodiment, the positive electrode active material includes one or more of lithium transition metal oxides, lithium-containing phosphates, and modified compounds thereof.

[0053] In any embodiment, the positive electrode plate further includes a second conductive agent, which includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0054] In any embodiment, the content of the polythiophene conductive polymer in the positive electrode film layer is 0.2-4%, optionally 0.5-3%, based on the total weight of the positive electrode film layer.

[0055] The fourth aspect of the present application provides a method for preparing a positive electrode sheet, comprising the following steps: coating the positive electrode slurry of the second aspect of the present application on at least one surface of the positive electrode collector, and obtaining an initial positive electrode sheet after drying and rolling; irradiating the initial positive electrode sheet obtained with a laser, and obtaining a positive electrode sheet after completion, wherein the laser wavelength is 445-505nm.

[0056] By using the above-mentioned polythiophene conductive polymer in the positive electrode plate and irradiating the positive electrode plate with blue light, photothermal conversion can be quickly performed, heating efficiency can be improved, and the adverse effects of blue light irradiation on the positive electrode active material can be reduced.

[0057] Through blue light irradiation, the polythiophene conductive polymer can be quickly heated, thereby releasing some stress, which is conducive to forming a positive electrode film layer with higher porosity, thereby reducing the amount of residual solvent and improving the electrolyte wettability of the positive electrode plate. Blue light irradiation can also remove substances such as dispersants and surfactants introduced during the processing of the positive electrode plate. At the same time, the heating efficiency is high, and the heating temperature is usually higher than the softening point of the positive electrode binder, thereby allowing the positive electrode binder to be evenly distributed in the thickness direction of the positive electrode plate, thereby helping to improve the cohesion and adhesion of the positive electrode plate, reduce the positive electrode resistance, and thus improve the rate performance of the battery.

[0058] In any embodiment, the laser is emitted continuously.

[0059] In any embodiment, the number of lasers is 1-10, and the total power is 100-2500W.

[0060] In any embodiment, the time for the initial positive electrode plate to pass through the laser spot is 0.05-0.5s.

[0061] In any embodiment, the vertical distance between the laser and the initial positive electrode plate is 5-15 cm.

[0062] A fifth aspect of the present application provides a battery cell, comprising the positive electrode sheet of the third aspect of the present application or the positive electrode sheet prepared by the preparation method of the fourth aspect of the present application.

[0063] A sixth aspect of the present application provides a battery, comprising the battery cell of the fifth aspect of the present application.

[0064] The seventh aspect of the present application provides an electrical device, which includes the battery of the sixth aspect of the present application.

[0065] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0067] Figure 1 It is a schematic diagram of the structure of a battery cell provided in some embodiments of the present application.

[0068] Figure 2 It is a schematic diagram of an exploded view of a battery cell provided in some embodiments of the present application.

[0069] Figure 3 It is a schematic diagram of the structure of the battery module provided in some embodiments of the present application.

[0070] Figure 4 It is a schematic diagram of the structure of the battery pack provided in some embodiments of the present application.

[0071] Figure 5 yes Figure 4 An exploded diagram of the battery pack is shown.

[0072] Figure 6 It is a schematic diagram of an electrical device provided in some embodiments of the present application.

[0073] Figure 7 1-1 and 1-2 are discharge curves of the batteries of Example 1-1 and Comparative Example 1-1 at different rates.

[0074] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1, battery pack; 2, upper box; 3, lower box; 4, battery module; 5, battery cell; 51, housing; 52, electrode assembly; 53, cover plate. DETAILED DESCRIPTION

[0075] Hereinafter, the embodiments of the polythiophene conductive polymer, positive electrode slurry, positive electrode sheet and preparation method thereof, battery cell, battery and electrical device of the present application will be specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0076] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0077] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0078] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0079] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0080] If not otherwise specified, in this application, the terms "first", "second", "third", "fourth", etc. are used to distinguish different objects rather than to describe a specific order or a primary and secondary relationship.

[0081] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0082] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0083] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0084] The term "alkyl" encompasses both straight chain and branched chain alkyl groups.

[0085] The term "alkylene" encompasses straight chain alkylene and branched chain alkylene.

[0086] The term "alkylalkoxy" encompasses straight chain alkylalkoxy and branched chain alkylalkoxy.

[0087] The term "hydrogen atom" covers 1 H(H), 2 H(D) and 3 H(T).

[0088] Throughout this manual, "#" indicates a connection location when it appears.

[0089] Throughout the present specification, the expression that a single bond passes through a ring or a ring system means that the single bond can be attached to any accessible position of the ring or the ring system.

[0090] In various places of this specification, the substituent of compound is disclosed with group or scope.It is clearly expected that this description includes each individual subcombination of the member of these groups and scope.For example, it is clearly expected that the term "C1-C6 alkyl" discloses C1, C2, C3, C4, C5, C6, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C6, C2-C5, C2-C4, C2-C3, C3-C6, C3-C5, C3-C4, C4-C6, C4-C5, C5-C6 alkyl individually.As other examples, it is clearly expected that the integer of 3-10 in the scope discloses 3,4,5,6,7,8,9 and 10 individually.Accordingly, other groups or scopes can be clearly expected.

[0091] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.

[0092] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.

[0093] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.

[0094] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0095] The battery cells provided in the embodiments of the present application include lithium-ion battery cells, lithium metal battery cells, etc., but the embodiments of the present application are not limited to this.

[0096] A battery cell generally includes an electrode assembly and an electrolyte. The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.

[0097] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0098] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to needs.

[0099] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0100] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0101] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0102] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the box body in any manner.

[0103] The positive electrode is an important component of the battery, and its performance has a crucial impact on the battery performance.

[0104] In order to further improve the energy density of the battery, the current common practice is to prepare a thick-coated positive electrode sheet or a high-density positive electrode sheet. However, the flexibility and processing performance of thick-coated and / or high-density positive electrode sheets are usually poor. When bending, winding or hot pressing the electrode assembly, the positive electrode film layer is prone to cracking or part of the positive electrode film layer falls off from the surface of the positive electrode current collector (i.e., powder loss). In addition, the residual solvent (such as water, N-methylpyrrolidone, etc.) in the positive electrode sheet is difficult to fully remove, which also makes the electrolyte wettability of the positive electrode film layer poor, making it difficult to fully distribute the electrolyte in the positive electrode film layer, and further affecting the rate performance of the battery.

[0105] Therefore, how to make the battery have good processing performance and rate performance while having high energy density is still a technical problem that needs to be solved.

[0106] In view of this, the inventors proposed a new polythiophene conductive polymer, which is used in the positive electrode sheet. After laser irradiation treatment, the processing performance of the positive electrode sheet can be improved, and the battery can also have both high energy density and good rate performance.

[0107] [Polythiophene conductive polymer]

[0108] The polythiophene conductive polymer provided in the embodiment of the present application includes a first structural unit represented by formula (1) and at least one of a second structural unit represented by formula (2), a third structural unit represented by formula (3) and a fourth structural unit represented by formula (4).

[0109]

[0110] R 11 Including C1-C8 alkyl or C1-C8 alkyl alkoxy, R 12 This includes a hydrogen atom or a C1-C3 alkyl group.

[0111] R 21 Including C1-C5 alkylene, R 22 includes a hydrogen atom or a C1-C3 alkyl group, and M includes a monovalent metal.

[0112] R 31 Including C1-C5 alkylene, R 32 This includes a hydrogen atom or a C1-C3 alkyl group.

[0113] R 41 Including C1-C5 alkylene, R 42 Including the residue of diisocyanate, R 43 Including C2-C6 alkylene, R 44 Including C1-C3 alkyl, R 45 Including hydrogen atom or C1-C3 alkyl, s≥1.42 It includes the residue of diisocyanate, that is, it can be diisocyanate O=C=N-R 42 —N=C=O is the remaining group after removing the isocyanate groups at both ends.

[0114] n1>0.

[0115] n2≥0, n3≥0, n4≥0, and n2+n3+n4>0.

[0116] In order to reduce the positive electrode resistance, the current common practice is to increase the amount of positive electrode conductive agent, such as conductive carbon, when preparing the positive electrode slurry, which can not only reduce the overall resistance of the positive electrode film layer, but also improve the rate performance of the battery. However, for high energy density battery systems, due to the large coating weight and high compaction density of the positive electrode sheet, the dispersion uniformity of the conductive carbon deteriorates, so the above method has limited effect on improving the internal resistance and rate performance of the battery, and the processing performance of the positive electrode sheet and the battery is still relatively poor.

[0117] The inventors have found that by making the positive electrode plate include the polythiophene conductive polymer provided in the embodiments of the present application, the cohesion and adhesion of the positive electrode plate can be improved, the electrolyte wettability of the positive electrode plate can be improved, and the processing performance and dynamic performance of the positive electrode plate can be improved, thereby enabling the battery to have both high energy density and good rate performance.

[0118] The positive electrode active material in the positive electrode plate has a low absorption rate for blue light, while the polythiophene conductive polymer provided in the embodiment of the present application has a high blue light absorption capacity. Therefore, by using the polythiophene conductive polymer provided in the embodiment of the present application in the positive electrode plate and irradiating the positive electrode plate with blue light, rapid photothermal conversion can be performed, the heating efficiency can be improved, and the adverse effects of blue light irradiation on the positive electrode active material can be reduced.

[0119] The polythiophene conductive polymer provided in the embodiment of the present application has good thermal conductivity. When it is used for the positive electrode plate and the positive electrode plate is irradiated with blue light, the polythiophene conductive polymer can be quickly heated, thereby releasing part of the stress, which is conducive to forming a positive electrode film layer with a higher porosity, thereby reducing the amount of residual solvent and improving the electrolyte wettability of the positive electrode plate; the positive electrode binder can also be softened during heating, so that the polythiophene conductive polymer and the positive electrode binder are more evenly distributed in the positive electrode film layer, thereby increasing the cohesion and adhesion of the positive electrode plate, and reducing the positive electrode resistance, thereby improving the dynamic performance of the positive electrode plate and the battery.

[0120] The polythiophene conductive polymer provided in the embodiment of the present application includes at least one of the second structural unit shown in formula (2), the third structural unit shown in formula (3) and the fourth structural unit shown in formula (4), wherein the second structural unit shown in formula (2), the third structural unit shown in formula (3) and the fourth structural unit shown in formula (4) have strong polar groups, such as hydroxyl groups, ester groups, carbamate groups, etc. These strong polar groups can red-shift the absorption wavelength of the polythiophene conductive polymer, thereby reducing the electrochemical band gap between the HOMO orbit and the LUMO orbit, thereby increasing the position of the maximum absorption peak of the polythiophene conductive polymer and improving the heating efficiency. The polythiophene conductive polymer provided in the embodiment of the present application also includes the first structural unit shown in formula (1), thereby making the positive electrode film layer have good electrolyte wettability and preventing the polythiophene conductive polymer from dissolving.

[0121] The polythiophene conductive polymer provided in the embodiment of the present application can be used in the positive electrode film layer to improve the flexibility and processing performance of the positive electrode sheet, especially the positive electrode sheet with thick coating and / or high compaction density. In addition, the polythiophene conductive polymer provided in the embodiment of the present application has conductivity and can provide a good electronic conductive path when used in the positive electrode sheet.

[0122] Therefore, the polythiophene conductive polymer provided in the embodiment of the present application can improve the processing performance of the positive electrode plate, improve the cohesion and adhesion of the positive electrode plate, and can also reduce the positive electrode resistance. When used in a battery, a battery with both high energy density and good rate performance can be obtained.

[0123] The polythiophene conductive polymer provided in the embodiment of the present application includes a first structural unit represented by formula (1) and at least one of a second structural unit represented by formula (2), a third structural unit represented by formula (3) and a fourth structural unit represented by formula (4). For example, in some embodiments, the polythiophene conductive polymer includes a first structural unit of formula (1) and a second structural unit of formula (2), in which case n2>0, n3=0, and n4=0; in some embodiments, the polythiophene conductive polymer includes a first structural unit of formula (1) and a third structural unit of formula (3), in which case n2=0, n3>0, and n4=0; in some embodiments, the polythiophene conductive polymer includes a first structural unit of formula (1), a third structural unit of formula (3), and a fourth structural unit of formula (4), in which case n2=0, n3>0, and n4>0; in some embodiments, the polythiophene conductive polymer includes a first structural unit of formula (1), a second structural unit of formula (2), a third structural unit of formula (3), and a fourth structural unit of formula (4), in which case n2>0, n3>0, and n4>0.

[0124] In some embodiments, the number average molecular weight of the polythiophene conductive polymer can be 3000-45000, for example, 3000, 4000, 5000, 7600, 8600, 10000, 12000, 15000, 18000, 20500, 23000, 25200, 28000, 30000, 34000, 40000, 45000, or any range thereof. In some embodiments, optionally, the number average molecular weight of the polythiophene conductive polymer can be 5000-34000, 7600-34000, 10000-34000, 5000-30000, 7600-30000, 10000-30000, 5000-28000, 7600-28000, 10000-28000, 5000-25200, 7600-25200, 10000-25200.

[0125] When the number average molecular weight of the polythiophene conductive polymer is within the above range, the positive electrode sheet can have good flexibility, thereby improving the processing performance of the positive electrode sheet and the battery; in addition, the positive electrode slurry can have good dispersibility and the polythiophene conductive polymer can be prevented from dissolving in the electrolyte, thereby better improving the performance of the battery.

[0126] When the number average molecular weight of the polythiophene conductive polymer is within the above range, the polythiophene conductive polymer can also have good thermal conductivity and electronic conductivity, thereby improving the heating efficiency and reducing the positive electrode resistance.

[0127] The number average molecular weight of the polythiophene conductive polymer has a well-known meaning in the art and can be measured using instruments and methods known in the art, for example, by gel permeation chromatography (GPC).

[0128] In some embodiments, R 11 A C4-C6 alkyl group or a C4-C6 alkylalkoxy group may be included.

[0129] In some embodiments, R 12 Hydrogen atoms may be included.

[0130] In some embodiments, R 11 Including C4-C6 alkyl or C4-C6 alkyl alkoxy, R 12 Including hydrogen atoms.

[0131] In some embodiments, R 21 A C1-C3 alkylene group may be included.

[0132] In some embodiments, R 22 Hydrogen atoms may be included.

[0133] In some embodiments, M may include Li and / or Na.

[0134] In some embodiments, R 21 Including C1-C3 alkylene, R 22 includes a hydrogen atom, and M includes Li and / or Na.

[0135] In some embodiments, R 31 A C1-C3 alkylene group may be included.

[0136] In some embodiments, R 32 Hydrogen atoms may be included.

[0137] In some embodiments, R 31 Including C1-C3 alkylene, R 32 Including hydrogen atoms.

[0138] In some embodiments, R 41 A C1-C3 alkylene group may be included.

[0139] In some embodiments, R 42 may represent the residue of an aliphatic, alicyclic and / or aromatic diisocyanate. 42 Including R a Substituted or unsubstituted C1-C6 alkylene, and one of the following groups:

[0140]

[0141]

[0142] # indicates the connection position, R a Each independently includes C1-C3 alkyl, R b Each independently includes a C1-C3 alkyl group, p represents an integer of 0-4, and q represents an integer of 0-6. When p is 0, it indicates that no substitution occurs at the position. When q is 0, it indicates that no substitution occurs at the position.

[0143] In some embodiments, R 43 The following groups may be included:

[0144]

[0145] In some embodiments, R 44 A methyl group may be included.

[0146] In some embodiments, R 45 Hydrogen atoms may be included.

[0147] In some embodiments, s can be 3-140, for example, 3, 10, 15, 20, 25, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, or any range thereof. In some embodiments, optionally, s can be 10-90, 10-80, 10-70, 10-60, 10-50, 20-90, 20-80, 20-70, 20-60, 20-50, 25-90, 25-80, 25-70, 25-60, 25-50.

[0148] [Preparation method of polythiophene conductive polymer]

[0149] The present application also provides a method for preparing the polythiophene conductive polymer.

[0150] The method at least comprises the steps of: providing a monomer compound or a precursor compound for preparing a polythiophene conductive polymer; preparing the polythiophene conductive polymer by an oxidative polymerization method using the monomer compound or the precursor compound. The oxidative polymerization method may be a chemical oxidative polymerization method or an electrochemical oxidative polymerization method. As an example, the oxidant of the chemical oxidative polymerization method may be FeCl3.

[0151] Those skilled in the art can select appropriate monomer compounds or their precursor compounds according to the target product.

[0152] For example, the first monomer compound used to form the first structural unit can be

[0153] As an example, the first monomer compound may include one or more of 3-butoxythiophene and 3-pentoxythiophene.

[0154] The first monomer compound can be obtained by alkyl chain replacement using methoxythiophene as a raw material. In some embodiments, methoxythiophene, alcohol (such as n-butanol, n-pentanol, etc.), anhydrous sodium bisulfate, and toluene are sequentially added to a reaction system in a nitrogen environment, heated and stirred at 80-100° C. for 2-5 hours, and the first monomer compound is obtained by reduced pressure distillation.

[0155] The second monomer compound used to form the second structural unit may be or its precursor compound R 23 Including C1-C8 alkyl.

[0156] As an example, the second monomer compound may include one or more of sodium thiophene-3-oxyacetate, lithium thiophene-3-oxyacetate, sodium 2-(thiophene-3-oxy)propionate, lithium 2-(thiophene-3-oxy)propionate, sodium 3-(thiophene-3-oxy)propionate, and lithium 3-(thiophene-3-oxy)propionate, and the precursor compound of the second monomer compound may include one or more of methyl thiophene-3-oxyacetate, ethyl thiophene-3-oxyacetate, methyl 2-(thiophene-3-oxy)propionate, ethyl 2-(thiophene-3-oxy)propionate, methyl 3-(thiophene-3-oxy)propionate, and ethyl 3-(thiophene-3-oxy)propionate.

[0157] The precursor compound of the second monomer compound can be obtained by alkyl chain replacement using methoxythiophene as a raw material. In some embodiments, in a nitrogen environment, methoxythiophene, ester (such as methyl glycolate, ethyl glycolate, methyl lactate, ethyl lactate, methyl β-hydroxypropionate, ethyl β-hydroxypropionate, etc.), anhydrous sodium bisulfate, and toluene are sequentially added to the reaction system and heated and stirred at 80-100° C. for 2-5 hours, and the precursor compound of the second monomer compound is obtained by reduced pressure distillation.

[0158] The second monomer compound can be prepared by placing a precursor compound of the second monomer compound in an alkaline solution, adjusting the pH, and stirring the solution to obtain the second monomer compound. The alkaline solution can include MOH, and M includes a monovalent metal, which can be Li and / or Na.

[0159] The third monomer compound used to form the third structural unit can be

[0160] As an example, the third monomer compound may include one or more of 3-thiophenecarbinol and 3-thiopheneethanol.

[0161] The fourth monomer compound used to form the fourth structural unit can be

[0162] The fourth monomer compound can be prepared by the following method: in a nitrogen environment, OH—(R 43 ) s —O—R 44 , diisocyanate OCN-R 42 —NCO is dissolved in a solvent (such as N,N-dimethylformamide), stirred at 70°C for 1-4h, and then added The reaction was continued at 70° C. with stirring for 4-8 hours under nitrogen protection to obtain a fourth monomer compound.

[0163] OH—(R 43 ) s —O—R 44It may include polyethylene glycol monomethyl ether (MPEG) and polybutylene glycol monomethyl ether.

[0164] In some embodiments, the method includes the steps of: dissolving a monomer compound or a precursor compound thereof in chloroform, then adding it to a chloroform solution of anhydrous FeCl3 under nitrogen protection, performing a polymerization reaction at 20-25°C (e.g., 24-96 hours), then adding methanol to precipitate the polymerization product, and finally extracting the precipitate in ethanol (e.g., 24-96 hours), and obtaining a polythiophene conductive polymer after drying.

[0165] In some embodiments, the method comprises the steps of: dissolving the first monomer compound, the second monomer compound and the third monomer compound in chloroform, then adding them to an anhydrous FeCl3 chloroform solution under nitrogen protection, performing a polymerization reaction at 20-25°C (e.g., 24-96h), then adding methanol to precipitate the polymerization product, and finally extracting the precipitate in ethanol (e.g., 24-96h); in a nitrogen environment, OH—(R 43 ) s —O—R 44 , diisocyanate OCN-R 42 —NCO is dissolved in a solvent (e.g., N,N-dimethylformamide), stirred at 65-75° C. for 1-4 hours, then the above-mentioned precipitate solution (the solvent may be N,N-dimethylformamide) is added, and the stirring reaction is continued at 65-75° C. for 4-8 hours under nitrogen protection, and then extracted with ethanol (e.g., 12-48 hours), and vacuum dried to obtain a polythiophene conductive polymer. The polythiophene conductive polymer includes a first structural unit, a second structural unit, a third structural unit, and a fourth structural unit.

[0166] In some embodiments, the method comprises the steps of: dissolving the first monomer compound, the precursor compound of the second monomer compound and the third monomer compound in chloroform, then adding them to a chloroform solution of anhydrous FeCl3 under nitrogen protection, performing a polymerization reaction at 20-25°C (e.g., 24-96 hours), then adding methanol to precipitate the polymerization product, and finally extracting the precipitate in ethanol (e.g., 24-96 hours); in a nitrogen environment, OH—(R 43 ) s —O—R 44 , diisocyanate OCN-R 42—NCO is dissolved in a solvent (e.g., N,N-dimethylformamide), stirred at 65-75°C for 1-4h, then the above precipitate solution (the solvent may be N,N-dimethylformamide) is added, and the stirring reaction is continued at 65-75°C for 4-8h under nitrogen protection, and then extracted with ethanol (e.g., 12-48h), and after vacuum drying, the product is dispersed in water, MOH is added to adjust the pH of the system (e.g., 7-9), and the polythiophene conductive polymer is obtained after stirring the reaction. The polythiophene conductive polymer includes a first structural unit, a second structural unit, a third result unit, and a fourth structural unit.

[0167] By adjusting parameters such as the type and concentration of monomers, the type and concentration of oxidants, reaction temperature, reaction time, etc., polythiophene conductive polymers with different molecular weights can be obtained.

[0168] [Cathode slurry]

[0169] The embodiment of the present application also provides a positive electrode slurry.

[0170] The positive electrode slurry includes a solvent and a non-solvent component, wherein the non-solvent component includes a positive electrode active material, a positive electrode binder and a positive electrode conductor, wherein the positive electrode conductor includes the polythiophene conductive polymer described above in the present application.

[0171] The polythiophene conductive polymer provided in the embodiments of the present application can be used in both non-aqueous positive electrode slurry and aqueous positive electrode slurry.

[0172] In some embodiments, the solvent includes a non-aqueous solvent, which may optionally include N-methylpyrrolidone, the positive electrode binder includes an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65. For example, n1 / (n1+n2+n3+n4) may be 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, or a range consisting of any of the above values.

[0173] Optionally, 0.40≤n1 / (n1+n2+n3+n4)≤0.60.

[0174] When n1 / (n1+n2+n3+n4) is within the above range, the dispersibility of the non-aqueous positive electrode slurry can be improved, the processing performance of the prepared positive electrode sheet can be improved, and the kinetic performance of the positive electrode sheet and the battery can also be improved.

[0175] In some embodiments, the positive electrode binder includes an oily binder, and as an example, the positive electrode binder may include one or more of polyvinylidene fluoride, polyimide, and polyurethane. The weight average molecular weight of polyvinylidene fluoride may be 50,000-2,000,000, thereby improving the bonding force of the positive electrode sheet and the processing performance of the positive electrode sheet.

[0176] In some embodiments, the positive electrode binder includes an oily binder, 0≤n2 / (n1+n2+n3+n4)≤0.25, for example, n2 / (n1+n2+n3+n4) can be 0, 0.05, 0.10, 0.15, 0.20, 0.25, or a range consisting of any of the above values.

[0177] In some embodiments, the positive electrode binder includes an oily binder, 0≤n2 / (n1+n2+n3+n4)≤0.10, optionally, n2 / (n1+n2+n3+n4)=0.

[0178] This can improve the dispersibility of the non-aqueous positive electrode slurry and also improve the dynamic performance of the positive electrode sheet and the battery.

[0179] In some embodiments, the positive electrode binder includes an oily binder, 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, for example, (n3+n4) / (n1+n2+n3+n4) can be 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, or a range consisting of any of the above values.

[0180] Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60.

[0181] When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0182] In some embodiments, 0≤n4 / (n3+n4)≤0.20, for example, n4 / (n3+n4) can be 0, 0.05, 0.10, 0.12, 0.15, 0.20, or a range consisting of any of the above values.

[0183] Optionally, 0<n4 / (n3+n4)≤0.15, 0<n4 / (n3+n4)≤0.12.

[0184] When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0185] In some embodiments, the solvent includes a non-aqueous solvent, which may optionally include N-methylpyrrolidone, the positive electrode binder includes an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65, 0≤n2 / (n1+n2+n3+n4)≤0.25, 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, and 0<n4 / (n3+n4)≤0.15.

[0186] In some embodiments, the solvent includes a non-aqueous solvent, which may optionally include N-methylpyrrolidone, the positive electrode binder includes an oily binder, and 0.40≤n1 / (n1+n2+n3+n4)≤0.60, 0≤n2 / (n1+n2+n3+n4)≤0.10, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, and 0<n4 / (n3+n4)≤0.15.

[0187] In some embodiments, the solvent includes a non-aqueous solvent, which may optionally include N-methylpyrrolidone, the positive electrode binder includes an oily binder, and 0.40≤n1 / (n1+n2+n3+n4)≤0.60, n2 / (n1+n2+n3+n4)=0, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, 0<n4 / (n3+n4)≤0.15.

[0188] In some embodiments, the solvent includes water, the positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25. For example, n1 / (n1+n2+n3+n4) can be 0.05, 0.08, 0.11, 0.15, 0.20, 0.22, 0.25, or a range consisting of any of the above values.

[0189] Optionally, 0.08≤n1 / (n1+n2+n3+n4)≤0.22, 0.11≤n1 / (n1+n2+n3+n4)≤0.22.

[0190] When n1 / (n1+n2+n3+n4) is within the above range, the dispersibility of the aqueous positive electrode slurry can be improved, the adhesion and processing performance of the prepared positive electrode sheet can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0191] In some embodiments, the positive electrode binder includes an aqueous binder. As an example, the positive electrode binder may include one or more of carboxymethyl cellulose and its derivatives, sodium alginate, polyacrylic acid and its derivatives, agarose, gelatin, carrageenan, xanthan gum, guar gum, polyvinyl alcohol, and polyacrylamide. When the positive electrode binder is within the above range, it is more environmentally friendly on the one hand, and can also improve the electrolyte affinity of the positive electrode film layer on the other hand.

[0192] In some embodiments, the positive electrode binder includes an aqueous binder, 0.15≤n2 / (n1+n2+n3+n4)≤0.45, for example, n2 / (n1+n2+n3+n4) can be 0.15, 0.20, 0.25, 0.30, 0.36, 0.40, 0.45, or a range consisting of any of the above values.

[0193] Optionally, 0.25≤n2 / (n1+n2+n3+n4)≤0.40, 0.25≤n2 / (n1+n2+n3+n4)≤0.36.

[0194] When n2 / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can be improved.

[0195] In some embodiments, the positive electrode binder includes an aqueous binder, 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, for example, (n3+n4) / (n1+n2+n3+n4) can be 0.30, 0.35, 0.40, 0.42, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, or a range consisting of any of the above values.

[0196] Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, 0.42≤(n3+n4) / (n1+n2+n3+n4)≤0.60.

[0197] When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0198] In some embodiments, the positive electrode binder includes an aqueous binder, 0≤n4 / (n3+n4)≤0.20, for example, n4 / (n3+n4) can be 0, 0.03, 0.04, 0.05, 0.08, 0.10, 0.12, 0.15, 0.20, or a range consisting of any of the above values.

[0199] Optionally, 0.04≤n4 / (n3+n4)≤0.15.

[0200] When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0201] In some embodiments, the solvent includes water, the positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25, 0.15≤n2 / (n1+n2+n3+n4)≤0.45, 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, and 0.04≤n4 / (n3+n4)≤0.15.

[0202] In some embodiments, the solvent includes water, the positive electrode binder includes an aqueous binder, and 0.08≤n1 / (n1+n2+n3+n4)≤0.22, 0.25≤n2 / (n1+n2+n3+n4)≤0.40, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, and 0.04≤n4 / (n3+n4)≤0.15.

[0203] In some embodiments, the solvent includes water, the positive electrode binder includes an aqueous binder, and 0.11≤n1 / (n1+n2+n3+n4)≤0.22, 0.25≤n2 / (n1+n2+n3+n4)≤0.36, 0.42≤(n3+n4) / (n1+n2+n3+n4)≤0.60, and 0.04≤n4 / (n3+n4)≤0.15.

[0204] In some embodiments, the positive electrode active material may include one or more of a lithium transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of lithium transition metal oxides may include one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates may include one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds. The present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for batteries may also be used.

[0205] In some embodiments, the positive electrode active material may include a lithium-containing phosphate, optionally including one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, and their respective modified compounds. These positive electrode active materials may be used alone or in combination of two or more.

[0206] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.

[0207] In some embodiments, the positive electrode slurry may further include a second conductive agent. As an example, the second conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0208] In some embodiments, the content of the polythiophene conductive polymer in the non-solvent component may be 0.2-4%, optionally 0.5-3%, based on the total weight of the non-solvent component.

[0209] The relative contents of different structural units in polythiophene conductive polymers can be measured by nuclear magnetic resonance spectroscopy (NMR).

[0210] [Positive electrode]

[0211] The embodiment of the present application also provides a positive electrode plate.

[0212] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor, and the positive electrode conductor includes the polythiophene conductive polymer described above in the present application.

[0213] The positive electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector.

[0214] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. Optionally, the aluminum foil may be 1060, 1070, 1100 or 1235, and the purity may be greater than 99%. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0215] In some embodiments, the thickness of the positive electrode current collector may be 10-20 μm.

[0216] In some embodiments, the positive electrode binder includes an oily binder, and as an example, the positive electrode binder may include one or more of polyvinylidene fluoride, polyimide, and polyurethane. The weight average molecular weight of polyvinylidene fluoride may be 50,000-2,000,000, thereby improving the bonding force of the positive electrode sheet and the processing performance of the positive electrode sheet.

[0217] In some embodiments, the positive electrode binder includes an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65. For example, n1 / (n1+n2+n3+n4) may be 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, or a range consisting of any of the above values.

[0218] Optionally, 0.40≤n1 / (n1+n2+n3+n4)≤0.60.

[0219] When n1 / (n1+n2+n3+n4) is within the above range, the uniformity of the positive electrode film layer can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0220] In some embodiments, the positive electrode binder includes an oily binder, 0≤n2 / (n1+n2+n3+n4)≤0.25, for example, n2 / (n1+n2+n3+n4) can be 0, 0.05, 0.10, 0.15, 0.20, 0.25, or a range consisting of any of the above values.

[0221] In some embodiments, the positive electrode binder includes an oily binder, 0≤n2 / (n1+n2+n3+n4)≤0.10, optionally, n2 / (n1+n2+n3+n4)=0.

[0222] This can improve the uniformity of the positive electrode film layer and also improve the dynamic performance of the positive electrode sheet and the battery.

[0223] In some embodiments, the positive electrode binder includes an oily binder, 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, for example, (n3+n4) / (n1+n2+n3+n4) can be 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, or a range consisting of any of the above values.

[0224] Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60.

[0225] When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0226] In some embodiments, the positive electrode binder includes an oily binder, 0≤n4 / (n3+n4)≤0.20, for example, n4 / (n3+n4) can be 0, 0.05, 0.10, 0.12, 0.15, 0.20, or a range consisting of any of the above values.

[0227] Optionally, 0<n4 / (n3+n4)≤0.15, 0<n4 / (n3+n4)≤0.12.

[0228] When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0229] In some embodiments, the positive electrode binder includes an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65, 0≤n2 / (n1+n2+n3+n4)≤0.25, 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, and 0<n4 / (n3+n4)≤0.15.

[0230] In some embodiments, the positive electrode binder includes an oily binder, and 0.40≤n1 / (n1+n2+n3+n4)≤0.60, 0≤n2 / (n1+n2+n3+n4)≤0.10, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, and 0<n4 / (n3+n4)≤0.15.

[0231] In some embodiments, the positive electrode binder includes an oily binder, and 0.40≤n1 / (n1+n2+n3+n4)≤0.60, n2 / (n1+n2+n3+n4)=0, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, 0<n4 / (n3+n4)≤0.15.

[0232] In some embodiments, the positive electrode binder includes an aqueous binder. As an example, the positive electrode binder may include one or more of carboxymethyl cellulose and its derivatives, sodium alginate, polyacrylic acid and its derivatives, agarose, gelatin, carrageenan, xanthan gum, guar gum, polyvinyl alcohol, and polyacrylamide. When the positive electrode binder is within the above range, it is more environmentally friendly on the one hand, and can also improve the electrolyte affinity of the positive electrode film layer on the other hand.

[0233] In some embodiments, the positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25. For example, n1 / (n1+n2+n3+n4) can be 0.05, 0.08, 0.11, 0.15, 0.20, 0.22, 0.25, or a range consisting of any of the above values.

[0234] Optionally, 0.08≤n1 / (n1+n2+n3+n4)≤0.22, 0.11≤n1 / (n1+n2+n3+n4)≤0.22.

[0235] When n1 / (n1+n2+n3+n4) is within the above range, the uniformity of the positive electrode film layer can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0236] In some embodiments, the positive electrode binder includes an aqueous binder, 0.15≤n2 / (n1+n2+n3+n4)≤0.45, for example, n2 / (n1+n2+n3+n4) can be 0.15, 0.20, 0.25, 0.30, 0.36, 0.40, 0.45, or a range consisting of any of the above values.

[0237] Optionally, 0.25≤n2 / (n1+n2+n3+n4)≤0.40, 0.25≤n2 / (n1+n2+n3+n4)≤0.36.

[0238] When n2 / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can be improved.

[0239] In some embodiments, the positive electrode binder includes an aqueous binder, 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, for example, (n3+n4) / (n1+n2+n3+n4) can be 0.30, 0.35, 0.40, 0.42, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, or a range consisting of any of the above values.

[0240] Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, 0.42≤(n3+n4) / (n1+n2+n3+n4)≤0.60.

[0241] When (n3+n4) / (n1+n2+n3+n4) is within the above range, the heating efficiency of the positive electrode sheet can be improved, the bonding force and cohesion of the positive electrode sheet can be enhanced, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0242] In some embodiments, the positive electrode binder includes an aqueous binder, 0≤n4 / (n3+n4)≤0.20, for example, n4 / (n3+n4) can be 0, 0.03, 0.04, 0.05, 0.08, 0.10, 0.12, 0.15, 0.20, or a range consisting of any of the above values.

[0243] Optionally, 0.04≤n4 / (n3+n4)≤0.15.

[0244] When n4 / (n3+n4) is within the above range, the processing performance of the positive electrode sheet and the battery can be improved, and the dynamic performance of the positive electrode sheet and the battery can also be improved.

[0245] In some embodiments, the positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25, 0.15≤n2 / (n1+n2+n3+n4)≤0.45, 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, and 0.04≤n4 / (n3+n4)≤0.15.

[0246] In some embodiments, the positive electrode binder includes an aqueous binder, and 0.08≤n1 / (n1+n2+n3+n4)≤0.22, 0.25≤n2 / (n1+n2+n3+n4)≤0.40, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60, and 0.04≤n4 / (n3+n4)≤0.15.

[0247] In some embodiments, the positive electrode binder includes an aqueous binder, and 0.11≤n1 / (n1+n2+n3+n4)≤0.22, 0.25≤n2 / (n1+n2+n3+n4)≤0.36, 0.42≤(n3+n4) / (n1+n2+n3+n4)≤0.60, and 0.04≤n4 / (n3+n4)≤0.15.

[0248] In some embodiments, the positive electrode conductive agent may further include a second conductive agent. As an example, the second conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0249] In some embodiments, the content of the polythiophene conductive polymer in the positive electrode film layer may be 0.2-4%, optionally 0.5-3%, based on the total weight of the positive electrode film layer.

[0250] In some embodiments, the content of the positive electrode conductive agent (including the polythiophene conductive polymer and the second conductive agent) in the positive electrode film layer may be 0.5-4%, based on the total weight of the positive electrode film layer.

[0251] In some embodiments, the content of the positive electrode active material in the positive electrode film layer may be 92-98%, based on the total weight of the positive electrode film layer.

[0252] In some embodiments, the content of the positive electrode binder in the positive electrode film layer may be 1-10%, based on the total weight of the positive electrode film layer.

[0253] The positive electrode active material may be a material known in the art, and the present application embodiment does not limit this. In some embodiments, the positive electrode active material includes a material that can reversibly extract and insert lithium ions.

[0254] In some embodiments, the positive electrode active material may include one or more of a lithium transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of lithium transition metal oxides may include one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates may include one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds. The present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for batteries may also be used.

[0255] In some embodiments, the positive electrode active material may include a lithium-containing phosphate, optionally including one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, and their respective modified compounds. These positive electrode active materials may be used alone or in combination of two or more.

[0256] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.

[0257] In some embodiments, the positive electrode active material may include a lithium-containing phosphate, and the volume distribution particle size Dv50 of the positive electrode active material may be 1-10 μm.

[0258] In some embodiments, the positive electrode active material may include a lithium-containing phosphate, and the surface density of the positive electrode sheet may be 0.2-0.8 g / 1540.25 mm 2 .

[0259] In some embodiments, the positive electrode active material may include a lithium-containing phosphate, and the compaction density of the positive electrode sheet may be 2.2-2.5 g / cm 3 This allows the battery to have a high energy density.

[0260] [Method for preparing positive electrode sheet]

[0261] The embodiment of the present application also provides a method for preparing a positive electrode plate.

[0262] The method comprises the following steps: coating the positive electrode slurry as described above on at least one surface of the positive electrode current collector, drying and rolling to obtain an initial positive electrode sheet; irradiating the initial positive electrode sheet obtained with a laser, and obtaining a positive electrode sheet after completion. The laser wavelength may be 445-505 nm.

[0263] The positive electrode active material in the positive electrode plate has a low absorption rate for blue light (wavelength of 445-505nm), while the polythiophene conductive polymer provided in the embodiment of the present application has a high blue light absorption capacity. Therefore, by using the polythiophene conductive polymer provided in the embodiment of the present application in the positive electrode plate and irradiating the positive electrode plate with blue light, rapid photothermal conversion can be performed, the heating efficiency can be improved, and the adverse effects of blue light irradiation on the positive electrode active material can be reduced.

[0264] Through blue light irradiation, the polythiophene conductive polymer can be quickly heated, thereby releasing some stress, which is conducive to forming a positive electrode film layer with higher porosity, thereby reducing the amount of residual solvent and improving the electrolyte wettability of the positive electrode plate. Blue light irradiation can also remove substances such as dispersants and surfactants introduced during the processing of the positive electrode plate. At the same time, the heating efficiency is high, and the heating temperature is usually higher than the softening point of the positive electrode binder, thereby allowing the positive electrode binder to be evenly distributed in the thickness direction of the positive electrode plate, thereby helping to improve the cohesion and adhesion of the positive electrode plate, reduce the positive electrode resistance, and thus improve the rate performance of the battery.

[0265] In some embodiments, the laser may be emitted continuously.

[0266] In some embodiments, the number of lasers may be 1-10, and the total power may be 100-2500W.

[0267] In some embodiments, the time for the initial positive electrode plate to pass through the laser spot can be 0.05-0.5s. The time for the initial positive electrode plate to pass through the laser spot refers to the time from the initial positive electrode plate contacting the laser spot to the laser spot leaving the laser spot and stopping irradiation.

[0268] In some embodiments, the vertical distance between the laser and the initial positive electrode plate can be 5-15 cm.

[0269] [Negative electrode]

[0270] The battery cell includes a negative electrode plate. The structure and composition of the negative electrode plate can be selected according to the type of the battery cell, and the embodiment of the present application is not limited to this.

[0271] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0272] The negative electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the negative electrode film layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector.

[0273] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As examples of metal foils, copper foil, copper alloy foil, aluminum foil, and aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0274] The negative electrode active material may adopt materials known in the art. In some embodiments, as an example, the negative electrode active material may include, but is not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy materials. Tin-based materials may include one or more of elemental tin, tin oxide, and tin alloy materials. The present application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0275] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0276] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). One or more.

[0277] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0278] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, the optional negative electrode conductive agent, the optional negative electrode binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0279] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.

[0280] In some embodiments, the negative electrode plate may include a negative electrode current collector and a first metal layer disposed on at least one surface of the negative electrode current collector, and the metal element in the first metal layer may include lithium element.

[0281] In some embodiments, the metal material in the first metal layer may include one or more of lithium element and lithium alloy.

[0282] The lithium alloy may be an alloy formed by metallic lithium and other metallic elements or non-metallic elements. As an example, the other metallic elements in the lithium alloy may include one or more of tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, and platinum, and the non-metallic elements in the lithium alloy may include one or more of boron, carbon, and silicon.

[0283] In some embodiments, the negative electrode sheet may include a negative electrode current collector but not include the first metal layer, so as to be assembled into a negative electrode metal-free battery cell.

[0284] In some embodiments, the negative electrode plate may also be made of a sheet (or foil) of lithium or a lithium alloy.

[0285] [Electrolytes]

[0286] The battery cell provided in the embodiment of the present application includes an electrolyte. The electrolyte plays a role of conducting ions between the positive electrode plate and the negative electrode plate. The present application does not specifically limit the type of electrolyte, which can be selected according to needs. For example, the electrolyte may include one or more of a solid electrolyte, a gel electrolyte, and a liquid electrolyte (i.e., an electrolyte).

[0287] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0288] The type of electrolyte salt is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the electrolyte salt may include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP) One or more.

[0289] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, the solvent may include one or more of an ester solvent, a sulfone solvent, and an ether solvent. As an example, the solvent may include, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB) , ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), diethyl sulfone (ESE), tetrahydrofuran (THF), 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxymethane, diethoxymethane, dipropoxymethane, 1,2-dimethoxyethane, 1,2-dimethoxypropane, 1,2-diethoxyethane, ethylene glycol methyl ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether. One or more.

[0290] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.

[0291] [Isolation film]

[0292] The battery cell provided in the embodiment of the present application may also include a separator. The separator may be disposed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent internal short circuits. The present application has no particular restrictions on the type of separator, and any known porous structure membrane with good chemical stability and mechanical stability may be selected.

[0293] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and polyimide. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0294] The preparation method of the battery cell provided in the embodiment of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0295] The present application also provides an electrical device, which includes a battery provided in the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0296] The electrical device can select a specific type of battery according to its usage requirements, for example, a battery cell, a battery module or a battery pack.

[0297] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0298] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0299] Example

[0300] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0301] Example 1-1

[0302] (1) Preparation of polythiophene conductive polymers

[0303] In a nitrogen environment, 1 mol of methoxythiophene, 1.5 mol of n-pentanol and 2 g of anhydrous sodium bisulfate were added to a reactor in sequence, heated and stirred at 110° C. for 3 h, and 3-pentyloxythiophene was obtained after reduced pressure distillation.

[0304] 3-pentyloxythiophene (the first monomer compound) and 3-thiophene methanol (the third monomer compound) were dry mixed at a molar ratio of 3:4, and about 10 g was dissolved in 100 mL of chloroform. Then, 500 mL of 0.2 mol / L anhydrous FeCl3 chloroform solution was added in a nitrogen environment, and the polymerization reaction was carried out at 25°C for about 24 hours. Then, methanol was added to the reaction system to precipitate the polymerization product, and the obtained precipitate was extracted in ethanol for 48 hours, and the intermediate was obtained after drying.

[0305] In a nitrogen environment, about 5 g of polyethylene glycol monomethyl ether (MPEG) with a molecular weight of 1000 and about 1 g of diphenylmethane diisocyanate are dissolved in 100 mL of N,N-dimethylformamide, stirred at 70°C for about 2 hours, and then 50 mL of N,N-dimethylformamide solution containing about 6 g of the above intermediate is added, and the mixture is stirred at 70°C for about 6 hours in a nitrogen environment; the reaction product is extracted with ethanol for 24 hours and vacuum dried to obtain a polythiophene conductive polymer. The polythiophene conductive polymer includes the first structural unit, the third structural unit and the fourth structural unit shown in Table 1, and n1:n2:(n3+n4) is 3:0:4, and n4 / (n3+n4) is 0.12. The number average molecular weight of the polythiophene conductive polymer is shown in Table 1. The relative content of different structural units in the polythiophene conductive polymer can be obtained by nuclear magnetic resonance spectroscopy (NMR).

[0306] (2) Preparation of positive electrode sheet

[0307] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 7 μm, polyvinylidene fluoride, polythiophene conductive polymer, and conductive carbon black (Super P) were uniformly dispersed in NMP according to a weight ratio of 96:2:1.5:0.5 to obtain a positive electrode slurry; the positive electrode slurry was coated on both sides of a 13 μm thick 1060 aluminum foil, then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.6 g / 1540.25 mm 2 , compacted density is 2.5g / cm 3 The initial positive electrode.

[0308] One of the positive electrode film layers of the above-mentioned initial positive electrode sheet is continuously irradiated with 495nm blue light composed of 5 lasers with a total power of 2000W for a residence time of 0.5s, and the vertical distance between the laser and the initial positive electrode sheet is 10cm; then the other positive electrode film layer of the initial positive electrode sheet is treated in the same way, and a positive electrode sheet is obtained after completion.

[0309] (3) Preparation of negative electrode sheet

[0310] The negative electrode active material artificial graphite, the conductive agent conductive carbon black (Super P), the thickener carboxymethyl cellulose, and the binder styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 96:1:1:2 to form a uniform negative electrode slurry; the negative electrode slurry is coated on both sides of a 6 μm thick copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.

[0311] (4) Preparation of electrolyte

[0312] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0313] (5) Preparation of isolation membrane

[0314] A porous polyethylene membrane was used as the separator.

[0315] (6) Preparation of batteries

[0316] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and the battery is obtained after vacuum packaging, standing, formation and other processes.

[0317] Example 1-2

[0318] The preparation method of the battery is similar to that of Example 1-1, except that the preparation processes of the polythiophene conductive polymer and the positive electrode are different.

[0319] (1) Preparation of polythiophene conductive polymers

[0320] In a nitrogen environment, 1 mol of methoxythiophene, 1.5 mol of n-butanol, 2 g of anhydrous sodium bisulfate, and 100 mL of toluene were added to the reactor in sequence, heated and stirred at 80° C. for 4 h, and 3-butoxythiophene was obtained after reduced pressure distillation.

[0321] 3-Butoxythiophene (the first monomer compound) and 3-thiophene methanol (the third monomer compound) were dry mixed at a molar ratio of 3:4, and about 10 g was dissolved in 100 mL of chloroform. Then, 500 mL of 0.2 mol / L anhydrous FeCl3 chloroform solution was added in a nitrogen environment, and the polymerization reaction was carried out at 25°C for about 48 hours. Then, methanol was added to the reaction system to precipitate the polymerization product, and the obtained precipitate was extracted in ethanol for 36 hours, and the intermediate was obtained after drying.

[0322] In a nitrogen environment, about 4 g of polyethylene glycol monomethyl ether (MPEG) with a molecular weight of 400 and about 1 g of diphenylmethane diisocyanate were dissolved in 100 mL of N,N-dimethylformamide, stirred at 70°C for 3 hours, and then 50 mL of N,N-dimethylformamide solution containing about 7 g of the above intermediate was added, and continued to stir at 70°C in a nitrogen environment for about 5 hours; the reaction product was extracted with ethanol for 48 hours and vacuum dried to obtain a polythiophene conductive polymer. The polythiophene conductive polymer includes the first structural unit, the third structural unit and the fourth structural unit shown in Table 1, and n1:n2:(n3+n4) is 3:0:4, and n4 / (n3+n4) is 0.12. The number average molecular weight of the polythiophene conductive polymer is shown in Table 1.

[0323] (2) Preparation of positive electrode sheet

[0324] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 5 μm, polyvinylidene fluoride, polythiophene conductive polymer, and conductive carbon black (Super P) were added into NMP at a weight ratio of 97:1:1.3:0.7 and uniformly dispersed to obtain a positive electrode slurry; the positive electrode slurry was coated on both sides of a 15 μm thick 1070 aluminum foil, and then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.65 g / 1540.25 mm 2 , compacted density is 2.45g / cm 3 The initial positive electrode.

[0325] One of the positive electrode film layers of the above-mentioned initial positive electrode sheet is continuously irradiated with 455nm blue light with a total power of 2500w composed of 4 lasers with a residence time of 0.3s, and the vertical distance between the laser and the initial positive electrode sheet is 5cm; then the other positive electrode film layer of the initial positive electrode sheet is treated in the same way, and a positive electrode sheet is obtained after completion.

[0326] Examples 1-3

[0327] The preparation method of the battery is similar to that of Example 1-1, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0328] In the process of preparing the polythiophene conductive polymer, 3-thiophene ethanol is used instead of 3-thiophene methanol. The polythiophene conductive polymer includes the first structural unit, the third structural unit and the fourth structural unit shown in Table 1, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 1.

[0329] Examples 1-4

[0330] The preparation method of the battery is similar to that of Example 1-1, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0331] In the process of preparing polythiophene conductive polymer, hexamethylene diisocyanate is used instead of diphenylmethane diisocyanate.

[0332] The polythiophene conductive polymer includes the first structural unit, the third structural unit and the fourth structural unit shown in Table 1, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are as shown in Table 1.

[0333] Examples 1-5

[0334] The preparation method of the battery is similar to that of Example 1-1, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0335] In the process of preparing polythiophene conductive polymer, dicyclohexylmethane diisocyanate is used instead of diphenylmethane diisocyanate.

[0336] The polythiophene conductive polymer includes the first structural unit, the third structural unit and the fourth structural unit shown in Table 1, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are respectively shown in Table 1.

[0337] Examples 1-6

[0338] The preparation method of the battery is similar to that of Example 1-1, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0339] When preparing the polythiophene conductive polymer, polyethylene glycol monomethyl ether (MPEG) and diphenylmethane diisocyanate were not added. The prepared polythiophene conductive polymer includes the first structural unit and the third structural unit shown in Table 1, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 1.

[0340] Examples 1-7

[0341] The preparation method of the battery is similar to that of Example 1-1, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0342] (1) Preparation of polythiophene conductive polymers

[0343] In a nitrogen environment, 1 mol of methoxythiophene, 1.5 mol of methyl lactate, 2 g of anhydrous sodium bisulfate and 100 mL of toluene were added to the reaction system in sequence, heated and stirred at 85° C. for 3.5 h, and methyl 2-(thiophene-3-oxy)propionate was obtained after reduced pressure distillation.

[0344] 3-pentyloxythiophene (the first monomer compound), methyl 2-(thiophene-3-oxy)propionate (the precursor compound of the second monomer compound), and 3-thiophene methanol (the third monomer compound) were dry mixed at a molar ratio of 5:0.5:4.5, and about 10 g was dissolved in 100 mL of chloroform. Then, 500 mL of 0.2 mol / L anhydrous FeCl3 chloroform solution was added in a nitrogen environment, and the polymerization reaction was carried out at 25°C for about 72 hours; methanol was then added to the reaction system to precipitate the polymerization product, and the obtained precipitate was extracted in ethanol for 36 hours, and the intermediate was obtained after drying.

[0345] 5 g of the intermediate was dispersed in water, NaOH was added to adjust the pH to 8.5, and stirring was continued for about 6 hours; then, the polythiophene conductive polymer was obtained by drying.

[0346] The polythiophene conductive polymer includes the first structural unit, the second structural unit and the third structural unit shown in Table 1, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are as shown in Table 1.

[0347] Examples 1-8

[0348] The preparation method of the battery is similar to that of Example 1-1, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0349] (1) Preparation of polythiophene conductive polymers

[0350] 3-pentyloxythiophene (the first monomer compound), methyl 2-(thiophene-3-oxy)propionate (the precursor compound of the second monomer compound), and 3-thiophene methanol (the third monomer compound) were dry mixed at a molar ratio of 5:1:4.5, and about 10 g was dissolved in 100 mL of chloroform. Then, 500 mL of 0.2 mol / L anhydrous FeCl3 chloroform solution was added in a nitrogen environment, and the polymerization reaction was carried out at 25°C for about 96 hours; methanol was then added to the reaction system to precipitate the polymerization product, and the obtained precipitate was extracted in ethanol for 36 hours, and the first intermediate was obtained after drying.

[0351] In a nitrogen environment, 5 g of polyethylene glycol monomethyl ether (MPEG) with a molecular weight of 1000 and 1 g of diphenylmethane diisocyanate were dissolved in 100 mL of N,N-dimethylformamide and stirred at 70°C for about 2 h. Subsequently, 50 mL of N,N-dimethylformamide solution containing 6 g of the above intermediate was added and continued to be stirred at 70°C in a nitrogen environment for about 6 h. The reaction product was extracted with ethanol for 24 h and vacuum dried to obtain a second intermediate.

[0352] 5 g of the second intermediate was dispersed in water, NaOH was added to adjust the pH to 8.5, and stirring was continued for 6 h; then, the polythiophene conductive polymer was obtained by drying.

[0353] The polythiophene conductive polymer includes the first structural unit, the second structural unit, the third structural unit and the fourth structural unit shown in Table 1, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are as shown in Table 1.

[0354] Examples 1-9 to 1-12

[0355] The preparation method of the battery is similar to that of Example 1-1, except that the number average molecular weight of the polythiophene conductive polymer is different, as shown in Table 3 for details.

[0356] Examples 1-13 to 1-17

[0357] The preparation method of the battery is similar to that of Example 1-1, except that the content and number average molecular weight of each structural unit in the polythiophene conductive polymer are different, as shown in Table 3 for details.

[0358] Examples 1-18 to 1-21

[0359] The preparation method of the battery is similar to that of Example 1-1, except that the content and number average molecular weight of each structural unit in the polythiophene conductive polymer are different, as shown in Table 3 for details.

[0360] When preparing the polythiophene conductive polymers of the above embodiments, one or more of the parameters such as the type and concentration of the monomer, the concentration of the oxidant FeCl3, the reaction temperature and the reaction time can be adjusted according to methods known in the art to obtain different number average molecular weights.

[0361] Comparative Example 1-1

[0362] The preparation method of the battery is similar to that of Example 1-1, except that the preparation process of the positive electrode plate is different.

[0363] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 7 μm, polyvinylidene fluoride, and conductive carbon black (Super P) were added to NMP at a weight ratio of 96:2:2 and uniformly dispersed to obtain a positive electrode slurry; the positive electrode slurry was coated on both sides of a 13 μm thick 1060 aluminum foil, then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.6 g / 1540.25 mm 2 , compacted density is 2.5g / cm 3 The positive electrode.

[0364] Comparative Example 1-2

[0365] The preparation method of the battery is similar to that of Example 1-1, except that the preparation process of the positive electrode plate is different.

[0366] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 7 μm, polyvinylidene fluoride, homopolymer polythiophene (the monomer is thiophene, and the number average molecular weight is between 15000-20000), and conductive carbon black (Super P) are added into NMP at a weight ratio of 96:2:1.3:0.7 and uniformly dispersed to obtain a positive electrode slurry; the positive electrode slurry is coated on both sides of a 13 μm thick 1060 aluminum foil, and then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.6 g / 1540.25 mm 2 , compacted density is 2.5g / cm 3 The initial positive electrode.

[0367] One of the positive electrode film layers of the above-mentioned initial positive electrode sheet is continuously irradiated with 495nm blue light composed of 5 lasers with a total power of 2000W for a residence time of 0.5s, and the vertical distance between the laser and the initial positive electrode sheet is 10cm; then the other positive electrode film layer of the initial positive electrode sheet is treated in the same way, and a positive electrode sheet is obtained after completion.

[0368] Test Section

[0369] (1) Resistance test of positive electrode

[0370] Cut the cold pressed positive electrode into 5cm×5cm, and then place it between the two electrodes of the resistance tester to test the resistance value of the positive electrode. The resistance tester can be Yuanneng Technology BER2500. The test temperature is 25℃.

[0371] (2) Adhesion test of positive electrode

[0372] The positive electrode sheet was washed with N-methylpyrrolidone to remove the positive electrode film layer on one side and dried, and then the single-sided coated positive electrode sheet was cut into 20mm×100mm test samples for use; the test sample was adhered to the side to be tested with double-sided tape, and compacted with a pressure roller to make the double-sided tape and the test sample completely fit; the other side of the double-sided tape was adhered to the stainless steel surface, and one end of the test sample was bent in the opposite direction with a bending angle of 180°; a high-speed rail tensile testing machine was used for testing, one end of the stainless steel was fixed to the lower fixture of the tensile testing machine, the bent end of the test sample was fixed to the upper fixture, the angle of the test sample was adjusted to ensure that the upper and lower ends were in a vertical position, and then the test sample was stretched at a speed of 50mm / min until the test sample was completely peeled off from the substrate, the displacement and force in the process were recorded, and the force when the force was balanced was taken as the bonding force of the positive electrode sheet.

[0373] (3) Porosity test of positive electrode sheet

[0374] The positive electrode sheet was cut into 20 circular sheets with a diameter of 14 mm, and the weight and thickness of the positive electrode sheet were recorded to calculate the volume density. The circular sheet was placed in the sample cup of the true density porosity tester, and the true volume of the positive electrode sheet was obtained by replacing it with helium, and combining Archimedes' law with Bohr's law, and then the true density of the positive electrode sheet was calculated. The porosity of the positive electrode sheet = (1-volume density / true density).

[0375] (4) Gram capacity test of positive electrode active materials

[0376] The positive electrode plate was washed with N-methylpyrrolidone to remove the positive electrode film layer on one side and dried, and then punched into a single-sided circular plate with a diameter of 14 mm and weighed; at the same time, the weight of the corresponding positive electrode current collector under the 14 mm diameter round plate was weighed to obtain the weight of the positive electrode film layer, and then the mass of the positive electrode active material was calculated.

[0377] The 2032 button battery is equipped with a negative electrode shell, nickel foam, 16mm diameter lithium sheet, 18mm diameter Celgard2325 isolation membrane, 0.1g 1mol·L -1 A 2032 button cell is assembled with LiPF6's EC:DMC:EMC (mass ratio 1:1:1) electrolyte, a 14mm diameter single-sided circular electrode piece, and a 2032 button cell supporting positive electrode shell.

[0378] The assembled button cell was left to stand for 12 hours before testing. The mass of the positive electrode active material multiplied by the theoretical gram capacity is the battery capacity, recorded as C. The button cell was charged to the upper cutoff voltage at a current of 0.1C, and then discharged to the upper cutoff voltage at a current of 0.1C. The gram capacity of the positive electrode active material is obtained by dividing the discharge capacity of the button cell by the mass of the positive electrode active material.

[0379] (5) Battery DC internal resistance (DCR) test

[0380] At 25°C, the batteries prepared in the examples and comparative examples were charged to a full charge state (100% SOC) at a constant current of 0.33C, and then discharged to 0.5Cn (Cn represents the battery capacity) at a constant current of 0.33C to adjust the battery to 50% SOC; the battery was left to stand for 30 minutes, and the voltage after the end of the standing was recorded as V1; then the battery was discharged at a current of 3C (recorded as I) for 30 seconds, and the discharge cut-off voltage was recorded as V2. The DC internal resistance DCR of the battery = (V1-V2) / I, V1 represents the end-of-standing voltage, V2 represents the discharge cut-off voltage, and I represents the discharge current.

[0381] (6) Battery rate performance test

[0382] At 25°C, the batteries prepared in each embodiment and comparative example were charged to 3.65V at a constant current of 0.33C, and then continued to be charged at a constant voltage to a current of 0.05C. After standing for 5 minutes, the battery was discharged to 2.5V at a constant current of 0.33C to obtain the discharge capacity of the battery at a rate of 0.33C; after the battery was stood for 30 minutes, it was charged to 3.65V at a constant current of 0.33C, and then charged to a current of 0.05C at a constant voltage. After standing for 5 minutes, the battery was discharged to 2.5V at a constant current of 3C to obtain the discharge capacity of the battery at a rate of 3C. The rate performance of the battery is represented by the ratio of the discharge capacity of the battery at a rate of 3C to the discharge capacity of the battery at a rate of 0.33C. The larger the ratio, the better the rate performance of the battery.

[0383] The test results of Examples 1-1 to 1-21 and Comparative Examples 1-1 to 1-2 are shown in Tables 2 and 3.

[0384] It can be seen from Tables 1 to 3 that the positive electrode plate provided in the embodiments of the present application has the characteristics of low resistance, high adhesion, high porosity and high specific capacity after being irradiated with blue light. When applied to batteries, it can reduce the internal resistance of the battery and improve the rate performance of the battery. Figure 7 1-1 and 1-1 are the discharge curves of the batteries of Example 1-1 and Comparative Example 1-1 at different rates. Figure 7 It can be seen that the battery prepared in Example 1-1 has a higher discharge capacity retention rate at a 3C rate.

[0385] The positive electrode conductive agent in the positive electrode plates of Examples 1-1 to 1-21 includes a functionalized polythiophene conductive polymer, which has a higher absorption rate for blue light wavelengths and a higher heating efficiency when irradiated with blue light, thereby better improving the distribution of the positive electrode binder in the positive electrode plate, thereby enhancing the bonding force and cohesion of the positive electrode plate, and also reducing the positive electrode resistance; stress can also be released during the blue light irradiation process, which is conducive to the formation of a positive electrode film layer with a higher porosity, thereby improving the electrolyte wettability of the positive electrode plate.

[0386] It can also be seen from the test results of Comparative Examples 1-2 that when the positive electrode conductive agent includes homopolymerized polythiophene, due to the lack of red-shifted functional groups, the wavelength corresponding to the maximum absorption peak of the positive electrode plate is not in the blue light wavelength range, which results in low blue light absorption rate, and thus the improvement effect on the positive electrode plate and the battery is not obvious.

[0387]

[0388]

[0389]

[0390] Example 2-1

[0391] The preparation method of the battery is similar to that of Example 1-1, except that the preparation processes of the polythiophene conductive polymer and the positive electrode are different.

[0392] (1) Preparation of polythiophene conductive polymers

[0393] In a nitrogen environment, 1 mol of methoxythiophene, 1.5 mol of ethyl glycolate, 2 g of anhydrous sodium bisulfate and 100 mL of toluene were added to the reaction system in sequence, heated and stirred at 90° C. for 3 h, and ethyl thiophene-3-oxyacetate was obtained after reduced pressure distillation.

[0394] 3-pentyloxythiophene (the first monomer compound), ethyl thiophene-3-oxyacetate (the precursor compound of the second monomer compound), and 3-thiophene methanol (the third monomer compound) were dry mixed in a molar ratio of 15:20:45, and about 10 g was dissolved in 100 mL of chloroform. Then, 500 mL of 0.2 mol / L anhydrous FeCl3 chloroform solution was added in a nitrogen environment, and the polymerization reaction was carried out at 25°C for about 48 hours; methanol was then added to the reaction system to precipitate the polymerization product, and the obtained precipitate was extracted in ethanol for 36 hours, and the first intermediate was obtained after drying.

[0395] In a nitrogen environment, about 8 g of polyethylene glycol monomethyl ether with a molecular weight of 6000 and about 2 g of diphenylmethane diisocyanate were dissolved in 100 mL of N,N-dimethylformamide, and stirred at 70°C for 3 h. Subsequently, 50 mL of N,N-dimethylformamide solution containing about 7 g of the above-mentioned first intermediate was added, and stirring was continued at 70°C in a nitrogen environment for about 5 h. The reaction product was extracted with ethanol for 36 h and vacuum dried to obtain a second intermediate.

[0396] 5 g of the second intermediate was dispersed in water, NaOH was added to adjust the pH to 8.5, and stirring was continued for about 6 hours; then the neutralized polythiophene conductive polymer was obtained by drying. The polythiophene conductive polymer includes the first structural unit, the second structural unit, the third structural unit and the fourth structural unit shown in Table 4, and n1:n2:(n3+n4) is 15:20:45, and n4 / (n3+n4) is 0.05. The number average molecular weight of the polythiophene conductive polymer is shown in Table 4.

[0397] (2) Preparation of positive electrode sheet

[0398] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 7 μm, sodium carboxymethyl cellulose, polythiophene conductive polymer, and conductive carbon black (Super P) were uniformly dispersed in deionized water according to a weight ratio of 96:2:1.3:0.7 to obtain a positive electrode slurry; the positive electrode slurry was coated on both sides of a 20 μm thick 1070 aluminum foil, and then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.7 g / 1540.25 mm 2 , compacted density is 2.4g / cm 3 The initial positive electrode.

[0399] One of the positive electrode film layers of the above-mentioned initial positive electrode sheet is continuously irradiated with 485nm blue light with a total power of 2500w composed of 10 lasers with a residence time of 0.25s, and the vertical distance between the laser and the initial positive electrode sheet is 15cm; then the other positive electrode film layer of the initial positive electrode sheet is treated in the same way, and a positive electrode sheet is obtained after completion.

[0400] Example 2-2

[0401] The preparation method of the battery is similar to that of Example 2-1, except that the preparation processes of the polythiophene conductive polymer and the positive electrode are different.

[0402] 3-pentyloxythiophene (the first monomer compound), methyl 2-(thiophene-3-oxy)propionate (the precursor compound of the second monomer compound), and 3-thiophene methanol (the third monomer compound) were dry mixed in a molar ratio of 15:20:45, and about 10 g was dissolved in 100 mL of chloroform. Then, 500 mL of 0.2 mol / L anhydrous FeCl3 chloroform solution was added in a nitrogen environment, and the polymerization reaction was carried out at 25°C for about 24 hours; then, methanol was added to the reaction system to precipitate the polymerization product, and the obtained precipitate was extracted in ethanol for 48 hours, and the first intermediate was obtained after drying.

[0403] In a nitrogen environment, about 6.5 g of polyethylene glycol monomethyl ether with a molecular weight of 500 and about 1.5 g of diphenylmethane diisocyanate were dissolved in 100 mL of N,N-dimethylformamide, and stirred at 70°C for 3 h. Subsequently, 50 mL of N,N-dimethylformamide solution containing about 7 g of the above-mentioned first intermediate was added, and stirring was continued at 70°C in a nitrogen environment for about 6 h. The reaction product was extracted with ethanol for 48 h and vacuum dried to obtain a second intermediate.

[0404] 5.5 g of the second intermediate was dispersed in water, LiOH was added to adjust the pH to 7.5, and stirring was continued for about 12 hours; then dried to obtain a polythiophene conductive polymer. The polythiophene conductive polymer includes the first structural unit, the second structural unit, the third structural unit and the fourth structural unit shown in Table 4, and n1:n2:(n3+n4) is 15:20:45, and n4 / (n3+n4) is 0.05. The number average molecular weight of the polythiophene conductive polymer is shown in Table 4.

[0405] (2) Preparation of positive electrode sheet

[0406] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 5 μm, sodium alginate, polythiophene conductive polymer, and conductive carbon black (Super P) were uniformly dispersed in deionized water at a weight ratio of 96.5:1.5:1.4:0.6 to obtain a positive electrode slurry; the positive electrode slurry was coated on both sides of a 20 μm thick 1070 aluminum foil, and then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.7 g / 1540.25 mm 2 , compacted density is 2.4g / cm 3 The initial positive electrode.

[0407] One of the positive electrode film layers of the above-mentioned initial positive electrode sheet is continuously irradiated with 505nm blue light composed of 8 lasers with a total power of 1500w for a residence time of 0.2s, and the vertical distance between the laser and the initial positive electrode sheet is 7.5cm; then the other positive electrode film layer of the initial positive electrode sheet is treated in the same way, and a positive electrode sheet is obtained after completion.

[0408] Example 2-3

[0409] The preparation method of the battery is similar to that of Example 2-2, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0410] In the process of preparing the polythiophene conductive polymer, 2-(thiophene-3-oxy) methyl lactate is used instead of 2-(thiophene-3-oxy) methyl propionate. The polythiophene conductive polymer includes the first structural unit, the second structural unit, the third structural unit and the fourth structural unit shown in Table 4, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 4.

[0411] Embodiment 2-4

[0412] The preparation method of the battery is similar to that of Example 2-2, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0413] In the process of preparing the polythiophene conductive polymer, 3-thiophene ethanol is used instead of 3-thiophene methanol. The polythiophene conductive polymer includes the first structural unit, the second structural unit, the third structural unit and the fourth structural unit shown in Table 4, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 4.

[0414] Embodiment 2-5

[0415] The preparation method of the battery is similar to that of Example 2-2, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0416] In the process of preparing the polythiophene conductive polymer, hexamethylene diisocyanate is used instead of diphenylmethane diisocyanate. The polythiophene conductive polymer includes the first structural unit, the second structural unit, the third structural unit and the fourth structural unit shown in Table 4, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 4.

[0417] Embodiment 2-6

[0418] The preparation method of the battery is similar to that of Example 2-2, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0419] In the process of preparing the polythiophene conductive polymer, dicyclohexylmethane diisocyanate is used instead of diphenylmethane diisocyanate. The polythiophene conductive polymer includes the first structural unit, the second structural unit, the third structural unit and the fourth structural unit shown in Table 4, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 4.

[0420] Embodiment 2-7

[0421] The preparation method of the battery is similar to that of Example 2-2, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0422] When preparing the polythiophene conductive polymer, the second monomer compound, polyethylene glycol monomethyl ether (MPEG) and diphenylmethane diisocyanate were not added. The prepared polythiophene conductive polymer includes the first structural unit and the third structural unit shown in Table 4, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 4.

[0423] Embodiment 2-8

[0424] The preparation method of the battery is similar to that of Example 2-2, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0425] When preparing the polythiophene conductive polymer, no second monomer compound was added. The prepared polythiophene conductive polymer includes the first structural unit, the third structural unit and the fourth structural unit shown in Table 4, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 4.

[0426] Embodiment 2-9

[0427] The preparation method of the battery is similar to that of Example 2-2, except that the structure and preparation process of the polythiophene conductive polymer are different.

[0428] When preparing the polythiophene conductive polymer, no second monomer compound was added. The prepared polythiophene conductive polymer includes the first structural unit, the third structural unit and the fourth structural unit shown in Table 4, and the content of each structural unit and the number average molecular weight of the polythiophene conductive polymer are shown in Table 4.

[0429] Examples 2-10 to 1-14

[0430] The preparation method of the battery is similar to that of Example 2-2, except that the number average molecular weight of the polythiophene conductive polymer is different, as shown in Table 6 for details.

[0431] Examples 2-15 to 1-18

[0432] The preparation method of the battery is similar to that of Example 2-2, except that the content and number average molecular weight of each structural unit in the polythiophene conductive polymer are different, as shown in Table 6 for details.

[0433] Examples 2-19 to 1-22

[0434] The preparation method of the battery is similar to that of Example 2-2, except that the content and number average molecular weight of each structural unit in the polythiophene conductive polymer are different, as shown in Table 6 for details.

[0435] Example 2-23

[0436] The preparation method of the battery is similar to that of Example 2-2, except that the pH of the second intermediate is adjusted to 7.5 with NaOH.

[0437] When preparing the polythiophene conductive polymers of the above embodiments, one or more of the parameters such as the type and concentration of the monomer, the concentration of the oxidant FeCl3, the reaction temperature and the reaction time can be adjusted according to methods known in the art to obtain different number average molecular weights.

[0438] Comparative Example 2-1

[0439] The preparation method of the battery is similar to that of Example 2-2, except that the preparation process of the positive electrode plate is different.

[0440] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 5 μm, sodium alginate, and conductive carbon black (Super P) were uniformly dispersed in deionized water at a weight ratio of 96.5:1.5:2 to obtain a positive electrode slurry; the positive electrode slurry was coated on both sides of a 20 μm thick 1070 aluminum foil, and then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.7 g / 1540.25 mm 2 , compacted density is 2.4g / cm 3 The positive electrode.

[0441] Comparative Example 2-2

[0442] The preparation method of the battery is similar to that of Example 2-2, except that the preparation process of the positive electrode plate is different.

[0443] The positive electrode active material lithium iron phosphate with a volume distribution particle size Dv50 of 5 μm, sodium alginate, homopolymerized polythiophene (the monomer is thiophene, and the number average molecular weight is between 15000-20000), and conductive carbon black (Super P) are uniformly dispersed in deionized water according to a weight ratio of 96.5:1.5:1.4:0.6 to obtain a positive electrode slurry; the positive electrode slurry is double-sided coated on a 20 μm thick 1070 aluminum foil, and then dried to evaporate the solvent, and then cold pressed to obtain a surface density of 0.7g / 1540.25mm 2 , compacted density is 2.4g / cm 3 The initial positive electrode.

[0444] One of the positive electrode film layers of the above-mentioned initial positive electrode sheet is continuously irradiated with 505nm blue light composed of 8 lasers with a total power of 1500w for a residence time of 0.2s, and the vertical distance between the laser and the initial positive electrode sheet is 7.5cm; then the other positive electrode film layer of the initial positive electrode sheet is treated in the same way, and a positive electrode sheet is obtained after completion.

[0445] The test methods of Examples 2-1 to 2-23 and Comparative Examples 2-1 to 2-2 were the same as those of Examples 1-1 to 1-21. The results are shown in Tables 5 and 6.

[0446] It can be seen from Tables 4 to 6 that the positive electrode plate provided in the embodiments of the present application has the characteristics of low resistance, high adhesion, high porosity and high gram capacity after being irradiated with blue light. When applied to batteries, it can reduce the internal resistance of the battery and improve the rate performance of the battery.

[0447] The positive electrode conductive agent in the positive electrode sheets of Examples 2-1 to 2-23 includes functionalized polythiophene conductive polymers, which have a higher absorption rate for blue light wavelengths and a higher heating efficiency when irradiated with blue light. This can better improve the distribution of the positive electrode binder in the positive electrode sheet, thereby enhancing the bonding and cohesive forces of the positive electrode sheet and reducing the positive electrode resistance. Stress can also be released during blue light irradiation, which is conducive to forming a positive electrode film layer with a higher porosity, thereby improving the electrolyte wettability of the positive electrode sheet.

[0448] It can also be seen from the test results of Comparative Example 2-2 that when the positive electrode conductive agent includes homopolymerized polythiophene, due to the lack of red-shifted functional groups, the wavelength corresponding to the maximum absorption peak of the positive electrode plate is not in the blue light wavelength range, which results in low blue light absorption rate, and thus the improvement effect on the positive electrode plate and the battery is not obvious.

[0449] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

[0450]

[0451]

[0452]

[0453]

Claims

1. A polythiophene conductive polymer, characterized in that: include: A first structural unit represented by formula (1); as well as at least one of the second structural unit represented by formula (2), the third structural unit represented by formula (3), and the fourth structural unit represented by formula (4), R 11 Including C1-C8 alkyl or C1-C8 alkyl alkoxy, R 12 including a hydrogen atom or a C1-C3 alkyl group; R 21 Including C1-C5 alkylene, R 22 includes a hydrogen atom or a C1-C3 alkyl group, and M includes a monovalent metal; R 31 Including C1-C5 alkylene, R 32 including a hydrogen atom or a C1-C3 alkyl group; R 41 Including C1-C5 alkylene, R 42 Including the residue of diisocyanate, R 43 Including C2-C6 alkylene, R 44 Including C1-C3 alkyl, R 45 Including hydrogen atom or C1-C3 alkyl, s≥1; n1>0; n2≥0, n3≥0, n4≥0, and n2+n3+n4>0.

2. The polythiophene conductive polymer according to claim 1, characterized in that The number average molecular weight of the polythiophene conductive polymer is 3000-45000, and can be optionally 5000-34000.

3. The polythiophene conductive polymer according to claim 1 or 2, characterized in that: The polythiophene conductive polymer satisfies at least one of the following conditions (1) to (13): (1)R 11 Including C4-C6 alkyl or C4-C6 alkylalkoxy; (2)R 12 Includes hydrogen atoms; (3)R 21 Including C1-C3 alkylene; (4)R 22 Includes hydrogen atoms; (5) M includes Li and / or Na; (6)R 31 Including C1-C3 alkylene; (7)R 32 Includes hydrogen atoms; (8)R 41 Including C1-C3 alkylene; (9)R 42 Including R a Substituted or unsubstituted C1-C6 alkylene, and one of the following groups: # indicates the connection position, R a Each independently includes C1-C3 alkyl, R b Each independently includes a C1-C3 alkyl group, p represents an integer of 0-4, and q represents an integer of 0-6; (10)R 43 Includes the following groups: (11)R 44 Including methyl; (12)R 45 Includes hydrogen atoms; (13)s is 3-140, and can be optionally 10-90.

4. The polythiophene conductive polymer according to any one of claims 1 to 3, characterized in that: n2>0,n3=0,n4=0;or, n2=0,n3>0,n4=0;or, n2=0,n3>0,n4>0;or, n2>0, n3>0, n4>0.

5. A positive electrode slurry, comprising a solvent and a non-solvent component, wherein the non-solvent component comprises a positive electrode active material, a positive electrode binder and a positive electrode conductor, characterized in that: The positive electrode conductive agent comprises the polythiophene conductive polymer according to any one of claims 1 to 4.

6. The positive electrode slurry according to claim 5, characterized in that The non-aqueous solvent may include N-methylpyrrolidone, the positive electrode binder may include an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65; Optionally, 0.40≤n1 / (n1+n2+n3+n4)≤0.60; and / or, Optionally, the positive electrode binder includes one or more of polyvinylidene fluoride, polyimide, and polyurethane.

7. The positive electrode slurry according to claim 6, characterized in that: 0≤n2 / (n1+n2+n3+n4)≤0.25, optionally, 0≤n2 / (n1+n2+n3+n4)≤0.10; and / or, 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60; and / or, 0≤n4 / (n3+n4)≤0.20, optionally, 0<n4 / (n3+n4)≤0.

15.

8. The positive electrode slurry according to claim 5, characterized in that: The solvent includes water, the positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25; Optionally, 0.08≤n1 / (n1+n2+n3+n4)≤0.22; and / or, Optionally, the positive electrode binder includes one or more of carboxymethyl cellulose and its derivatives, sodium alginate, polyacrylic acid and its derivatives, agarose, gelatin, carrageenan, xanthan gum, guar gum, polyvinyl alcohol, and polyacrylamide.

9. The positive electrode slurry according to claim 8, characterized in that: 0.15≤n2 / (n1+n2+n3+n4)≤0.45, optionally, 0.25≤n2 / (n1+n2+n3+n4)≤0.40; and / or, 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60; and / or, 0≤n4 / (n3+n4)≤0.20, optionally, 0.04≤n4 / (n3+n4)≤0.

15.

10. The positive electrode slurry according to any one of claims 5 to 9, characterized in that: The positive electrode active material includes one or more of lithium transition metal oxides, lithium-containing phosphates, and their respective modified compounds; and / or, The positive electrode slurry further includes a second conductive agent, wherein the second conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; and / or, The content of the polythiophene conductive polymer in the non-solvent component is 0.2-4%, optionally 0.5-3%, based on the total weight of the non-solvent component.

11. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode film layer comprises a positive electrode active material, a positive electrode binder and a positive electrode conductor, and the positive electrode conductor comprises the polythiophene conductive polymer according to any one of claims 1 to 4.

12. The positive electrode sheet according to claim 11, characterized in that: The positive electrode binder includes an oily binder, and 0.35≤n1 / (n1+n2+n3+n4)≤0.65; Optionally, 0.40≤n1 / (n1+n2+n3+n4)≤0.60; and / or, Optionally, the positive electrode binder includes one or more of polyvinylidene fluoride, polyimide, and polyurethane.

13. The positive electrode sheet according to claim 12, characterized in that: 0≤n2 / (n1+n2+n3+n4)≤0.25, optionally, 0≤n2 / (n1+n2+n3+n4)≤0.10; and / or, 0.35≤(n3+n4) / (n1+n2+n3+n4)≤0.65, Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60; and / or, 0≤n4 / (n3+n4)≤0.20, optionally, 0<n4 / (n3+n4)≤0.

15.

14. The positive electrode sheet according to claim 11, characterized in that: The positive electrode binder includes an aqueous binder, and 0.05≤n1 / (n1+n2+n3+n4)≤0.25; Optionally, 0.08≤n1 / (n1+n2+n3+n4)≤0.22; and / or, Optionally, the positive electrode binder includes one or more of carboxymethyl cellulose and its derivatives, sodium alginate, polyacrylic acid and its derivatives, agarose, gelatin, carrageenan, xanthan gum, guar gum, polyvinyl alcohol, and polyacrylamide.

15. The positive electrode sheet according to claim 14, characterized in that: 0.15≤n2 / (n1+n2+n3+n4)≤0.45, optionally, 0.25≤n2 / (n1+n2+n3+n4)≤0.40; and / or, 0.30≤(n3+n4) / (n1+n2+n3+n4)≤0.80, Optionally, 0.40≤(n3+n4) / (n1+n2+n3+n4)≤0.60; and / or, 0≤n4 / (n3+n4)≤0.20, optionally, 0.04≤n4 / (n3+n4)≤0.

15.

16. The positive electrode sheet according to any one of claims 11 to 15, characterized in that: The positive electrode active material includes one or more of lithium transition metal oxides, lithium-containing phosphates, and their respective modified compounds; and / or, The positive electrode plate further includes a second conductive agent, wherein the second conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; and / or, The content of the polythiophene conductive polymer in the positive electrode film layer is 0.2-4%, and optionally 0.5-3%, based on the total weight of the positive electrode film layer.

17. A method for preparing a positive electrode sheet, characterized in that: The steps include: Applying the positive electrode slurry according to any one of claims 5 to 10 on at least one surface of the positive electrode current collector, drying and rolling to obtain an initial positive electrode sheet; The initial positive electrode sheet is obtained by laser irradiation, and a positive electrode sheet is obtained after completion, wherein the laser wavelength is 445-505nm.

18. The preparation method according to claim 17, characterized in that: The laser is emitted in a continuous manner; and / or, The number of lasers is 1-10 and the total power is 100-2500W; and / or, The time for the initial positive electrode plate to pass through the laser spot is 0.05-0.5s; and / or, The vertical distance between the laser and the initial positive electrode plate is 5-15 cm.

19. A battery cell, characterized in that: A positive electrode sheet comprising the positive electrode sheet described in any one of claims 11 to 16 or a positive electrode sheet prepared by the preparation method described in any one of claims 17 to 18.

20. A battery, characterized in that: Comprising the battery cell as claimed in claim 19.

21. An electrical device, characterized in that: Comprising the battery of claim 20.

Citation Information

Patent Citations

  • A polythiophene derivative composite conductive negative electrode active material and preparation method thereof

    CN109004191A

  • Processes for preparing conductive macromolecular polythiophenes

    US20040171790A1

  • Polythiophenes, water-soluble conductive polymer using same, and method for producing same

    WO2014007299A1